Perception of blindness and blinding eye conditions in rural communities (2006)
Purpose: The purpose of this qualitative study was to explore the causes and management of blindness and blinding eye conditions as perceived by rural dwellers of two Yoruba communities in Oyo State, Nigeria. Methods: Four focus group discussions were conducted among residents of Iddo and Isale Oyo, two rural Yoruba communities in Oyo State, Nigeria. Participants consisted of sighted, those who were partially or totally blind and community leaders. Ten patent medicine sellers and 12 traditional healers were also interviewed on their perception of the causes and management of blindness in their communities. Findings: Blindness was perceived as an increasing problem among the communities. Multiple factors were perceived to cause blindness, including germs, onchocerciasis and supernatural forces. Traditional healers believed that blindness could be cured, with many claiming that they had previously cured blindness in the past. However, all agreed that patience was an important requirement for the cure of blindness. The patent medicine sellers' reports were similar to those of the traditional healers. The barriers to use of orthodox medicine were mainly fear, misconception and perceived high costs of care. There was a consensus of opinion among group discussants and informants that there are severe social and economic consequences of blindness, including not been able to see and assess the quality of what the sufferer eats, perpetual sadness, loss of sleep and dependence on other persons for daily activities. Conclusion: Local beliefs associated with causation, symptoms and management of blindness and blinding eye conditions among rural Yoruba communities identified have provided a bridge for understanding local perspectives and basis for implementing appropriate primary eye care programs.